Intra-Ocular Pressure Measurements by Canon TX-F Pulsair Tonometer and Goldmann Applanation Tonometer - Naqaish Sadiq , Ali Tayyab ,Sulman Jaffar , Amena Masrur (Journal of Rawalpindi Medical College, 2016)
Background: To analyze the limits of agreement for the intra- and inter-session measurements of intra-ocular pressure as measured by the Goldmann applanation tonometer and the Canon TX-F non-contact pulsair tonometer Methods: For this cross sectional study, 138 eyes of 138 cases of age > 16 years with no evidence of glaucomatous changes were recruited. Cases with astigmatism ≥ ±3.0 Diopters, corneal refractive surgery and scars, ocular inflammations, anterior chamber dysgenesis were excluded. Intra-ocular pressure was measured with the Goldmann Applanation Tonometer proceeded by Canon TX-F non-contact tonometer on day 1 and day 7. Bland-Altman plots were created for method comparison, with correlation and repeated measures ANOVA analysis using MedCalc Version 13.0.6.0 Results: On day 1 the intra-ocular pressures were 16.29 (±3.10) mmHg and 16.56 (±3.09) mmHg and on day 7, 16.26 (±3.09) and 16.56 (±3.09) mmHg respectively from Goldmann Tonometer and Canon TX-F. Independent t-test & Repeated measures ANOVA showed no statistically significant differences in repeated IOP measurements on days 1 and 7 between and across the instrument measurements. Method-comparison showed strong limits of agreements. Conclusion: The Canon TX-F offers precision and accuracy that allows its results to be interchanged with those of the Goldmann Applanation Tonometer.